The teacher training in the educational use of TIC: an approach from educational politics (Praxis Educativa, 2012)
In recent years, the huge development of digital information and the communication technologies, which have been presented as the panacea of education, has grasped a great dose of attention. In this article, after expressing our position in front of technology, we briefly characterize an optimistic discourse around the digital technologies that not only has failed to fill the expectations raised but, by focussing in their immense possibilities, has constantly neglected the rest of the components of the educational system. Subsequently we address the initial and in-service professional development of teachers that configures itself as a fundamental factor to transform and improve the educational practice, this time with the aid of the ICT. The analysis of the policy and the practice of promotion of the use of ICT carried out in Catalonia, in the last 25 years, allows us to glimpse the inadequacy of the initial and in-service professional development of teachers, not only to respond to the educational needs of the current society, but for achieving the own objectives of the Computers in Education Program.
Keywords: educational innovation; digital competence; educational improvement; professional development